Perancangan dan Implementasi Sistem Informasi Manajemen Persediaan Barang Dagang - Iis Pradesan (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
Information technology is a matter that cannot be separated from business activities at all levels of management in a company, one level of management that utilizes information technology, namely parts / inventory in trading companies, this level is one very important part in controlling entry and get out of goods, because when a problem occurs in the process of processing inventory data it will have an impact on the process of buying and selling and of course will also have an impact on the company's strategic plan. Given the importance of this matter, this study aims to design and implement information technology-based merchandise inventory management information systems, with the output of this research being a web application based application.